2016
DOI: 10.1103/physrevlett.116.057601
|View full text |Cite
|
Sign up to set email alerts
|

Large Spin-Wave Bullet in a Ferrimagnetic Insulator Driven by the Spin Hall Effect

Abstract: Due to its transverse nature, spin Hall effects (SHE) provide the possibility to excite and detect spin currents and magnetization dynamics even in magnetic insulators. Magnetic insulators are outstanding materials for the investigation of nonlinear phenomena and for novel low power spintronics applications because of their extremely low Gilbert damping. Here, we report on the direct imaging of electrically driven spin-torque ferromagnetic resonance (ST-FMR) in the ferrimagnetic insulator Y3Fe5O12 based on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 47 publications
(96 reference statements)
5
57
0
Order By: Relevance
“…Differences in nonlinear damping as a function of sample size and dimension govern even whether or not an anti-damping torque is capable of generating large-angle magnetic precession [Tiberkevich and Slavin, 2007; Demidov et al ., 2011; Duan et al ., 2014]. Nonlinear modes excited by spin-transfer torques have been observed for much larger sample sizes in low-damping materials like yttrium iron garnet (YIG) than in higher-damping metallic systems [Jungfleisch et al ., 2016b]. …”
Section: Large-angle Magnetization Dynamics Driven By Interfacial mentioning
confidence: 99%
“…Differences in nonlinear damping as a function of sample size and dimension govern even whether or not an anti-damping torque is capable of generating large-angle magnetic precession [Tiberkevich and Slavin, 2007; Demidov et al ., 2011; Duan et al ., 2014]. Nonlinear modes excited by spin-transfer torques have been observed for much larger sample sizes in low-damping materials like yttrium iron garnet (YIG) than in higher-damping metallic systems [Jungfleisch et al ., 2016b]. …”
Section: Large-angle Magnetization Dynamics Driven By Interfacial mentioning
confidence: 99%
“…Although from the symmetry point of view, the torques induced by the Oersted field and the field-like component of STT are indistinguishable from each other, in our work we confirm that the driving field is dominated by the Oersted contribution by repeating the measurement with Pt and Ta. Recently, several groups have studied the CI-FMR in YIG/Pt both theoretically [20,21] and experimentally [22][23][24]. Using the theoretical model built by Chiba et al [21], Schreier et al did the first experiment on in-plane CI-FMR in YIG/Pt and identified the current-induced torque by the symmetry and the lineshape of the signals [22].…”
mentioning
confidence: 99%
“…Sklenar et al then repeated the experiment for an outof-plane external magnetic field [23]. Very recently, Jungfleisch et al imaged the current-driven magnetization precession in YIG/Pt at resonance condition with Brillouin light scattering spectroscopy and argued that uniform precession is no longer applicable at high microwave power [24]. The behaviour of CI-FMR in YIG/HM, however, should depend on the thickness of the films [20], which is one aspect that remains under explored to the best of our knowledge.…”
mentioning
confidence: 99%
“…An example of a system that has recently benefited from a complete in-plane study is the magnetic insulator system YIG and the well understood spin Hall metal Pt configured into a ST-FMR experiment. 22,23 Here, the complete in-plane angular dependence uncovered an additional dc voltage contribution that was not included in the theoretical model; 43 the extra dc signal is thought to arise from the on-resonant microwave heating of the sample which in turn provided incoherent spin pumping. The incoherent spin pumping was detected as a dc signal via the inverse spin Hall effect.…”
Section: Antiferromagnets: Materials Of Interestmentioning
confidence: 99%
“…One example is where the spin Hall magnetoresistance in a Pt metal deposited on the ferrimagnetic insulator Y 3 Fe 5 O 12 (YIG) lead to rectification. [21][22][23] A second example of note is STT generated by the Rashba effect in Py/Ag/Bi as opposed to spin Hall effects. 24,25 For this work, the experimental set-up used to detect the AMR rectification is shown in Fig.…”
Section: Spin Torque Ferromagnetic Resonance: Metrology For Spin Hmentioning
confidence: 99%